Pengaruh Financial Stability, Financial Distress, Kepemilikan Institusional, Dan Komite Audit Terhadap Kecurangan Laporan Keuangan - Rizqi Ramadhan Situmorang; Andri Syahputra (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
This study was conducted to analyze Financial Stability, Financial Distress, Institutional Ownership, and Audit Committee on Financial Statement Fraud. The study was conducted on Infrastructure sector companies listed on the Indonesia Stock Exchange in 2020-2024. The methodology used is panel data regression. Sample selection was carried out using a purposive sampling method so that 23 companies were obtained as research samples and the period studied was 5 years, namely from 2020 to 2024, resulting in 115 samples. The data used were taken from audited financial statements and annual reports published by each company studied. Hypothesis testing was conducted using the Eviews series 12 application. The results of the study indicate that Financial Stability partially affects Financial Statement Fraud, Financial Distress does not affect Financial Statement Fraud, Institutional Ownership does not affect Financial Statement Fraud, and the Audit Committee does not affect Financial Statement Fraud. Financial Stability, Financial Distress, Institutional Ownership, and Audit Committees simultaneously influence Financial Statement Fraud.